Greenhouse gas measurement from smallholder production systems: guidelines for static chamber method - Sapkota, Tek Bahadur; Rai, M.; Singh, L.K.; Gathala, Mahesh Kumar; Jat, Mangi Lal; Sutaliya, Jhabar Mal; Bijarniya, Deepak; Jat MK; Jat, Kumar Raj; Parihar CM; Kapoor P; Jat HS; et al. (2014)
Renewed interest in quantifying greenhouse gas emissions from soil has led to development and application of multitude of techniques. But, chamber-based flux measurement technique is most common and frequently used method for GHG flux measurement in smallholder production systems. Despite the apparent conceptual simplicity of chamber-based methods, chamber design, deployment, and data analyses can have marked effects on the quality of the flux data derived from chamber-based measurement. This also have implications on making comparisons of GHGs emissions from the studies by various researchers even within similar cropping systems and management practices. Therefore, harmonization of GHGs emission studies by chamber based method is necessary. This synthesis provides standard guidelines to scientists involved in GHG quantification by using chamber based methods as well as to facilitate inter study comparison.